An Exploration Of Certain Properties Of Chaotic Dynamics In G-Spaces - Jawad, Kadhim (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
Let X be a topological G-space and let Ϝn (X) be the n-fold symmetric product of X, for any positive integer n. Let f∶ X→ X be a function, we consider the induced functions Ϝn(f): Ϝn(X) → Ϝn(X). In this paper we presented some chaotic properties like: Transitive, Mixing, Weakly Mixing, Totally Transitive, Exact, Strongly Transitive and Chaotic. We investigate the relationship between systems f and Ϝn (f) for the above properties.